2016
DOI: 10.1016/j.apjtm.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence on radiosensitivity of lung glandular cancer cells when ERCC1 gene silenced by targeted siRNA

Abstract: The radiation sensitivity of lung glandular tumor could be improved after the ERCC1 gene was silenced by siRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The presence of the ERCC1 rs735482 genotype is associated with an increased risk of acute radiotoxicity in HNC 23 . Mechanistically, ERCC1 silencing by targeted siRNA was shown to increase the radiosensitivity of lung cancer cells 28 . Additionally, Keam et al showed that some variants in ERCC1 , XPD , and XRCC belonged to a single haplotype block 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the ERCC1 rs735482 genotype is associated with an increased risk of acute radiotoxicity in HNC 23 . Mechanistically, ERCC1 silencing by targeted siRNA was shown to increase the radiosensitivity of lung cancer cells 28 . Additionally, Keam et al showed that some variants in ERCC1 , XPD , and XRCC belonged to a single haplotype block 29 …”
Section: Discussionmentioning
confidence: 99%
“…23 Mechanistically, ERCC1 silencing by targeted siRNA was shown to increase the radiosensitivity of lung cancer cells. 28 Additionally, Keam et al showed that some variants in ERCC1, XPD, and XRCC belonged to a single haplotype block. 29 Cisplatin-based chemotherapy generates intra-and inter-strand cross-links that are repaired by nucleotide excision repair pathway; consequently, mutations in NER genes, including ERCC1, lead to hypersensitivity to cisplatin in cultured cells.…”
Section: Discussionmentioning
confidence: 99%